(untitled) (Research, Society and Development, 2020)
Aim: to analyze the dimensions of patient safety culture from a multiprofessional perspective. Methodo: an exploratory descriptive study with a quantitative approach conducted in two hospitals in southern Brazil. The study included 108 workers from the multiprofessional health team. Data collection was performed from August to December 2017, using the Survey on Patient Safety Culture questionnaire as an instrument. Data analysis was performed by descriptive and analytical statistics. Results: the beliefs, attitudes and perceptions of health professionals regarding patient safety still present important weaknesses in the evaluated hospitals. Even considering the general perception of the safety culture as adequate, we highlight the weaknesses regarding staff sizing, non-punitive responses to errors and teamwork among the units. Conclusions: the consolidation of patient safety is a strategy for quality improvement and process remodeling, enabling safe practices to qualify multiprofessional work and at the same time guarantee the quality of care, which is a patient right.